1999
DOI: 10.1073/pnas.96.23.13506
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and amphetamine-regulated transcript in the rat vagus nerve: A putative mediator of cholecystokinin-induced satiety

Abstract: Cocaine-and amphetamine-regulated transcript (CART) is widely expressed in the central nervous system. Recent studies have pointed to a role for CART-derived peptides in inhibiting feeding behavior. Although these actions have generally been attributed to hypothalamic CART, it remains to be determined whether additional CART pathways exist that link signals from the gastrointestinal tract to the central control of food intake. In the present study, we have investigated the presence of CART in the rat vagus ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 45 publications
12
82
1
2
Order By: Relevance
“…The CCK-1 receptor is not well expressed in rostral regions of the ganglion, and here there were few examples of colocalization. A common population of nodose ganglion neurons is already known to express CCK-1, Ob-R, OX-R1, and CART immunoreactivity (Broberger et al, 1999;Burdyga et al, 2003), and consistent with this we also found CB1 to be colocalized with Ob-R, OX-R1, and CART (data not shown). Neurons in the mid and caudal regions of the rat nodose ganglion project to the gastrointestinal tract (Green and Dockray, 1988), and to determine whether this population of neurons corresponded to those expressing CB1, we studied the distribution after retrograde labeling of cells by injection of True Blue into the stomach and duodenum.…”
Section: Immunohistochemical Localization Of Cb1supporting
confidence: 90%
See 2 more Smart Citations
“…The CCK-1 receptor is not well expressed in rostral regions of the ganglion, and here there were few examples of colocalization. A common population of nodose ganglion neurons is already known to express CCK-1, Ob-R, OX-R1, and CART immunoreactivity (Broberger et al, 1999;Burdyga et al, 2003), and consistent with this we also found CB1 to be colocalized with Ob-R, OX-R1, and CART (data not shown). Neurons in the mid and caudal regions of the rat nodose ganglion project to the gastrointestinal tract (Green and Dockray, 1988), and to determine whether this population of neurons corresponded to those expressing CB1, we studied the distribution after retrograde labeling of cells by injection of True Blue into the stomach and duodenum.…”
Section: Immunohistochemical Localization Of Cb1supporting
confidence: 90%
“…Recent evidence suggests that the same neurons also express Ob-R and OX-R1 (Buyse et al, 2001;Burdyga et al, 2002Burdyga et al, , 2003Peiser et al, 2002), and the putative peptide transmitter CART (Broberger et al, 1999). Previous studies have found little evidence to indicate dietary modulation of the expression of the relevant genes (Broberger et al, 1999. The main finding of the present study is that this neuronal population expresses the CB1 receptor, and importantly expression is increased by fasting and downregulated by CCK.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Double labeling with an antibody to CCK revealed the presence of close anatomical appositions between labeled vagal afferent fibers and CCK-ir enteroendocrine cells in the lamina propria of duodenum and jejunum (Berthoud and Patterson, 1996). Together with the demonstration that vagal afferents express CCK-1 receptor (Moriarty et al, 1997;Broberger et al, 1999;Patterson et al, 2002) and numerous functional studies, these findings strongly suggest that luminal nutrients, particularly lipids and proteins activate vagal afferents via release of CCK from adjacent enteroendocrine cells (Smith et al, 1985;Geary, 2004;Raybould et al, 2006).…”
Section: Upper Small Intestine: Cck Gip and "Taste In The Gut"mentioning
confidence: 71%
“…A sua demonstração no nervo vago e em gânglios nodosos víscero-sensoriais, e a co-expressão com o receptor CCK A são compatíveis com um papel na sensação visceral gastrintestinal reguladora da saciedade pós-prandial (171). Os neurônios imuno-reagentes para CART estão encontrados em vários níveis no SNC.…”
Section: Transcrito Regulado Por Cocaína E Anfetamina (Cart)unclassified